BIMBINGAN BELAJAR MENGGUNAKAN METODE PEMBELAJARAN AKSI (AKTIF, KREATIF, SANTAI DAN INOVATIF) DI DESA NAGACIPTA - Halimatussadiyah, Halimatussadiyah; Lubis, Rabiyannur; Irham, Irham (Universitas Islam 45 Bekasi, 2024)
This community benefit program points to supply consider direction to understudies at MI Al-Islamiyah 02 Naga Cipta Town, Serang Baru Area, Bekasi Rule. The objects of this movement were course VI understudies at MI Al-ISLAMIYAH 02 Nagabuat Town and the action was carried out for 3 days. The strategy utilized in this mentoring is the Activity strategy (Dynamic, Inventive, Loose and Imaginative). The presence of this direction program can offer assistance understudies within the learning process, such as giving help and guidance within the learning handle which points to extend students' eagerness and intrigued in learning. The comes about of this AKSI strategy can encourage participation and collaboration between people which can create way better and more inventive arrangements and can increment students' positive states of mind which can make a comfortable and agreeable learning climate. The learning handle as of now carried out by instructors tends to be overwhelmed by the educator, in this manner, utilizing the Activity strategy, a modern learning climate can be made.